Inner Cover, Editorial Board, From the Desk of the Editors - Jubir, Admin (Journal of Business Innovation and Research, 2023)
JUBIR is published by Magister of Management, UPN "Veteran" Yogyakarta as a medium to study various phenomena and research related to business innovation in a broad sense. JuBIR is published twice a year, every April and October. Editors accept articles written in English. The editor has the right to shorten or improve the writing to be published without changing the meaning and content. Opinions expressed in the articles are the authors’ personal opinion, not the opinion of the Editorial Board.